Pendaftaran Hak Atas Tanah Lebak Lebung Warisan Berdasarkan Undang-Undang Pokok Agraria dan Peraturan Pelaksanaannya - Abdul Hamid Usman (Universitas Batanghari Jambi, 2022)
In South Sumatra Province, there is a traditional institution that is still alive today, namely the business of catching fish and other aquatic products in the Lebak Lebung area. Lebak Lebung is an area of land that declines around the river which is naturally in the rainy season all waterlogged so that it becomes a breeding ground for fish and other aquatic biota. Meanwhile, in summer this area of land becomes dry, making it a place for people to work on rice fields or other businesses. In this area of land there is a fairly deep part where the water does not dry out even in summer, this is called Lebung. There are two types of Lebak Lebung, namely the General Lebak Lebung which is located on the Tanah Marga and the Lebak Lebung Heritage which is located on customary land. Based on the provisions of Article 19 of the UUPA and its implementing regulations, any land rights must be registered with the local Land Office, including the rights to the Lebak Lebung Heritage land. Therefore, the center of discussion in this paper is the implementation of the registration of land rights in Lebak Lebung Heritage based on the Basic Agrarian Law (UUPA) and its implementing regulations. By taking into account the UUPA and its implementing regulations as well as the opinions of experts in related fields, the implementation of the registration of land rights in Lebak Lebung Heritage based on the Basic Agrarian Law and its implementing regulations is carried out by means of the land owner submitting an application for confirmation of conversion and registration of former Indonesian land rights to the local Land Office, provided that: 1) Regarding the rights that have been described in a land title certificate, the application must be accompanied by: (a) proof of evidence (if any, a letter of measurement is also included); (b) proof of valid citizenship of the person having the right; (c) a statement from the applicant that the land is agricultural land which is the area of Lebak Lebung Heritage, that is, if this is not evident from the proof of the rights mentioned above. After the requirements are declared complete, then announced to the public for two months. If there is no objection, the Head of the Land Office confirms the conversion of the land rights by registering the rights concerned in the land book. At the request of the entitled, then a certificate of land rights is issued; 2) Meanwhile, for rights that are not described in a land title certificate, the application must be accompanied by: (a) proof of entitlement, namely proof of Indonesian plantation/verponding tax certificate or proof of letter of granting rights by the competent authority (if any, a measurement letter is also included); (b) a letter from the Village Head, confirmed by the local Camat, confirming the letter or letters of proof of the right, explaining that the land is agricultural land which is the Lebak Lebung Heritage area, explaining who has the right, if any, accompanied by a derivative letter - letter of sale and purchase of the land; (c) proof of valid citizenship of the person who has the right. After the requirements are declared complete, then an examination is carried out by the Land Examination Committee A, the results are announced to the public for two months. If there is no objection, the applicant is given a recognition of rights. In the decision letter on the recognition of the right, it is confirmed that the conversion of the right to property rights, building use rights, business use rights, or use rights will be registered by the Head of the relevant Land Office. Then at the request of the entitled, then a certificate of land rights is issued.